2020
DOI: 10.1155/2020/2046947
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the BRAF, NRAS, and C-KIT Genes of Patients Diagnosed with Melanoma in Colombia Population

Abstract: Introduction. Mutations in the BRAF, NRAS, and C-KIT genes have been associated with the histopathological characteristics of melanoma. Likewise, the incidence of each of these subtypes changes according to the geographical origin of the population analyzed. Objective. To determine the mutation frequency in exons 11 and 15 of the BRAF gene, exons 1 and 2 of the NRAS gene, and exons 11, 13, and 17 of the C-KIT gene and to relate it with histological subtypes in patients from a region with high levels of ultravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(67 reference statements)
0
5
1
Order By: Relevance
“…Of the total sample, 62.3% were men, and male pre-dominance was maintained in all melanoma subtypes, being more marked in nodular and acral lentiginous (26.0 and 12.5%, respectively). This differs slightly from that reported in the literature, where there is usually a slightly higher incidence in women and in Lentigo Maligna, results that do not agree with previous local studies 10,11 but do with international research 12,13 Similar to that reported globally are also observed in relation to the mean age which ranges between 57-63 years of age 14,15 however a study conducted in Japan reported an increase in cases in populations under 50 years 9 as illustrated in Table 1.…”
Section: Discussioncontrasting
confidence: 85%
“…Of the total sample, 62.3% were men, and male pre-dominance was maintained in all melanoma subtypes, being more marked in nodular and acral lentiginous (26.0 and 12.5%, respectively). This differs slightly from that reported in the literature, where there is usually a slightly higher incidence in women and in Lentigo Maligna, results that do not agree with previous local studies 10,11 but do with international research 12,13 Similar to that reported globally are also observed in relation to the mean age which ranges between 57-63 years of age 14,15 however a study conducted in Japan reported an increase in cases in populations under 50 years 9 as illustrated in Table 1.…”
Section: Discussioncontrasting
confidence: 85%
“…An interesting aspect is that reported subtypes of melanoma in the Latin-American region are different to those reported in high-incidence regions. In the Colombian population, several studies have shown that lentigo malignant melanoma is the most frequent with 36.41-52%, followed by acral lentiginous melanoma with 20-24.71% incidence (15). The frequency of melanoma in Latin America varies according to the studied population.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, previous studies indicated the mutually exclusive mutations among BRAF, NRAS, and NF1. 10-12 In terms of 10 patients with KIT mutation in the present study, 2 had NF1 mutations, while neither of them had BRAF and NRAS mutations. Median follow-up duration was 16.9 months (range, 0.9-70.1).…”
Section: Resultsmentioning
confidence: 50%